Treatment outcomes of T and natural‐killer/T‐cell lymphoma with ifosfamide, carboplatin and etoposide chemotherapy. Issue 9 (28th April 2022) - Tay, Tricia; Somasundaram, Nagavalli; Lim, Cindy; Khoo, Lay Poh; Goh, Allan Zhi Kai; Lee, Yuh Shan; Liu, Xin; Tao, Miriam; Quek, Richard; Farid, Mohamad; Poon, Eileen; Chan, Jason Y. S.; et al.
Abstract: Background: Contemporary data of peripheral T‐cell lymphoma (PTCL) and natural‐killer/T‐cell lymphoma (NKTL) patients treated with ifosfamide, carboplatin and etoposide (ICE) are limited. Aims: We performed a retrospective analysis to estimate outcomes of ICE‐treated PTCL and NKTL patients at three tertiary cancer centres in Singapore. Methods and Results: Patients were identified through lymphoma databases from National Cancer Centre Singapore (NCCS), National University Hospital, Singapore (NUHS), and Singapore General Hospital (SGH). Responses and survival outcomes were determined from electronic medical records. A total of 75 patients with a median age of 50 were included. ICE was used as first‐line treatment in 14 patients (19%) and as subsequent lines of treatment in 61 patients (81%). The overall response rates (ORR) for all patients was 63% (40% complete response [CR]). The ORR and CR in the first line were 86% and 64% respectively. At a median follow‐up duration of 71.0 months, the median progression‐free (PFS) and overall survival (OS) for all patients were 4.4 months (95%CI, 2.7–6.0) and 16 months (95%CI, 8.3–45.4) respectively. Conclusion: In summary, ICE showed high ORR but poor PFS in relapsed/refractory PTCL and NKTL. ORR of ICE in the first line setting appears better than real‐world CHOP data and warrants further study.